A nexus between Green HRM (GHRM), Supply Chain Performance (SCP) and Business Performance (BP): The mediating role of Supply Chain Organizational Learning (SCOL) - Muafi; Rizqi Adhyka Kusumawati (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: This study tests and analyzes the relationship pattern (nexus) of Green HRM, SCP, and BP. In addition, this study also tests the mediation role of SCP in analyzing the relationship between GHRM and BP and the mediation role of SCP in analyzing the relationship between SCOL and BP. Design/methodology: This study uses survey method. The survey is distributed to owners/managers of courier service SMEs in two provinces (Special Region of Yogyakarta and East Java) in Indonesia. The sampling technique is conducted purposively with 165 respondents. The data analysis technique uses AMOS 23. Findings: SCOL has a positive effect on SCP and BP and mediates the effect of SCP on BP. The most interesting about the findings is GHRM has no effect on SCP and BP and SCP does not mediate GHRM on BP. Research limitations/implications: Researcher use purposive sampling which has limitation of not being able to generalize the population in two provinces, namely Special Region of Yogyakarta and East Java. This is also not ideal approach to evaluate the impact of GHRM on SCP and BP and the impact of SCOL on SCP and BP. Courier service SMEs in this study have not implemented GHRM in ideal manner so they are unable to conclude the results in a comprehensive and transparent manner. Managerial Implication: Companies need to consider aspects related to the courier service industry, namely digitalization of information and green innovation so their contribution can be seen in improving whole business performance. In addition, it is necessary to divide SMEs that have practiced GHRM and those that are not so they can make strategies and policies related to GHRM, SCP, BP and SCOL. It is also necessary to examine other aspects in improving the business sustainability of courier services, namely the complexity and service strategy orientation. SMEs who have more SCOL strategy will better implement GHRM practices associated with SCP and BP. This is important since competition in the courier service industry is getting tougher especially when faced with foreign competitors who already have global service standards. Theory Implication: This study contributes the theory enrichment of SCOL aspect in mediating the relationship pattern between SCP and BP. This study also provides theoretical contributions namely GHRM has no effect on SCP and BP and SCP does not mediate GHRM on BP. Originality/value: Study which examines the role of SCOL, especially when it is related to GHRM, SCP and BP is still limited in Asia. SME owners in the courier service industry rarely have good data integration in the system. The implementation of SC is starting from upstream to downstream processes so that SMEs need a well-planned and integrated SCOL in each work unit which ultimately have an impact on SCP and BP.
Keywords: 650; Green HRM (GHRM); Supply Chain Organizational Learning (SCOL); Supply Chain Performance (SCP); Business Performance (BP)